Pengenalan Buku Kas Sebagai Upaya Pengaturan keuangan keluarga Kepada Para Ibu Rukun Tetangga 29 Kelurahan Sawah Lebar Kota Bengkulu - Susena, Karona Cahya; Nasution, Suswati; Hidayah, Nenden Restu; Yustanti, Nirta Vera; Ariantara, Yudi (Jurnal Dehasen Mengabdi, 2022)
Management of family finances is very important, considering the many problems that occur due to the lack of skills in managing family finances. What often happens is an imbalance between income and expenditure, the term is "big pegs than poles." As a result, it can lead to disputes between husband and wife which causes a loss of the husband's level of trust in his wife. The absence of bookkeeping results in uncontrolled spending, depleted for expenses that are not important and are not a priority scale. Likewise, the problems that occurred to women who were members of RT.29 arisan, Sawah Lebar Village, Bengkulu City, where most of the members were completely unfamiliar with financial bookkeeping. So that there is an imbalance between income and expenditure, unskilled in setting the priority scale of family finances, weaknesses in planning expenses, weaknesses in recording and managing family financial cashflows. This community service activity is proposed with a solution in the form of training in family financial management with simple bookkeeping, namely a cash book. This activity aims to provide skills to mothers in managing family finances. The expected target is the skills of mothers in terms of managing finances. The method used is training by giving lectures or explanations as well as training on financial management and family financial management exercises/practices with simple cash book equipment that has been prepared.